A formal framework supporting the specification of the interactions between agents - Mokhati, Farid (Informatica (Ljubljana), 2006)
In this paper we present a formal framework supporting the translation of interactions between agents (the interactions are described with the help of the RCA formalism) in a Maude specification. Based on rewriting logic, the formal and object-oriented language Maude supports formal specification and programming for a wide range of applications. The main motivations of our work are essentially: (1) to formally specify the behavior of multi-agent systems (2) to provide a solid basis for their verification and validation. The translation process is illustrated by means of a real case study.
Keywords: večagentni sistemi; interakcije; prevajanje; translation; vrednotenje